Estudo de cintiladores CdWO4 produzidos por diferentes rotas de síntese - Costa, Michelle Silveira Vilanova (2014)
This work aimed the production of cadmium tungstate (CdWO4-CWO) using co-precipitation, hydrothermal with heating with microwaves and sol-gel methods, using PVA (polyvinyl alcohol). A mixed route using co-precipitation followed by hydrothermalization was also tested. The comparison between the efficiency of the route to produce single phase, as well as the luminescent output of the samples, was performed. CdWO4 is a scintillator material highly functional due to its chemical and thermal stability and high stopping power for X-rays. This material has been widely used for computer tomography. Through the analysis of the crystal phase of the produced materials, it was verified that the samples presented major phase CdWO4. In some cases, minor phases were also observed, in proportions that depended on the synthesis method employed. Calcination and washing procedures have also influenced the amount of secondary phases in the samples. The best crystallization results were achieved by the co-precipitation route, followed by microwave heating. The luminescent performance of CdWO4 was investigated by photoluminescence measurements. The measurements were performed in emission mode and presented only the intrinsic emission of the material. The sample with the best light output was CWO produced by co-precipitation route.